At the northern frontier of Near Eastern archaeology - Humboldt-Kolleg (Turnhout, Belgium)
vii, 587 sayfa
Keywords: “35 papers, originally presented by an international group of researchers at a conference held in Venice in January 2013, present the results of the last 20 years of archaeological research about the pre-classical cultures of the Caucasus and Anatolia, and analyse the latter in the wider framework of their changing relations with those of the Ancient Near East and of the Eurasian steppes. The volume covers a wide chronological span - from the late 5th to the early 1st millennium BC, and includes contributions about a wide range of topics (reports of archaeological excavations and surveys, chronology, economy, social organisation of the ancient populations, technology, long-distance exchange of raw materials and artefacts, archaeometallurgy, landscape archaeology, etc.). According to the most recent developments of research, these are investigated in a remarkably interdisciplinary perspective. The participation to the conference of well-recognised experts working not only in different countries of the Southern Caucasus and in Anatolia (in present-day Georgia, Armenia, Azerbaijan, and Turkey) but also in the North-Caucasian republics of the present-day Russian Federation offered a rare opportunity to compare and discuss recent trends of archaeological research in these different regions. Therefore, this volume represents a fundamental contribution to both Near Eastern and Caucasian Archaeology.” --